Production and Characterization of Natural Dyes for Ecoprinting Leather from the Extracts of Three Mangrove Species - Wehandaka Pancapalaga; Erny Ishartati; Titik Ambarwati (Jurnal Sylva Lestari, 2023)
This study aimed to determine the potential of Rhizophora mucronata, Maclura cochinchinensis, and Ceriops tagal extracts as a dye for ecoprinting leather. The parameters evaluated were color values (L*, a*, and b*), Fourier-Transform Infrared Spectroscopy (FTIR) analysis, and ecoprinting leather color fastness. The results showed that R. mucronata extract produced a brownish-red color with the L*, a*, and b* values of 17.53, 36.27, and 30.19, respectively. M. cochinchinensis extract produced a brownish-yellow color with the L*, a*, and b* values of 34.59, 31.87, and 58.61, while C. tagal extract produced a reddish-brown color with the L*, a*, and b* values of 32.36, 36.80, and 34.06. The results of FTIR analysis of the three mangrove extracts identified several functional groups such as O-H stretch, C=O stretch, C=C aromatic, C-O-C stretch, and C-N stretch. The color fastness of wet rubbing showed that R. mucronata and C. tagal extracts have a value of 4, indicating a good category. In contrast, M. cochinchinensis extract has a value of 5, with an excellent tegory. It showed that the extracts of R. mucronata, M. cochinchinensis, and C. tagal could be used for leather coloring with the ecoprinting method. Keywords: Ceriops tagal, ecoprinting leather, Maclura cochinchinensis, natural dyes, Rhizophora mucronata